Catalyst for purification of exhaust gas

CN122995907APending Publication Date: 2026-10-27CATALER CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480090122.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是,在稀燃气氛下,难以从NOx中夺取氧,存在无法净化NOx的问题

Benefits of technology

[0018]关于这里所公开的废气净化用催化剂[6],在上述废气净化用催化剂[1]~[5]的任一项中,上述下层前部的废气流动方向上的涂敷长度为上述基材的全长的30%以上60%以下,上述下层后部的废气流动方向上的涂敷长度为上述基材的全长的60%以上90%以下。由此,能够稳定地以高水平兼顾稀燃气氛下的NOx吸储性能的提高与化学计量比~富燃气氛下的NOx净化性能的提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995907A_ABST
    Figure CN122995907A_ABST
Patent Text Reader

Abstract

The present invention provides an exhaust gas purification catalyst having improved NOx storage capacity under a lean burn gas atmosphere. The exhaust gas purification catalyst (100) disclosed herein includes a substrate (10) and a catalyst layer (20). The catalyst layer (20) includes a lower layer (22), an intermediate layer (24), and an upper layer (26). The upper layer (26) contains Rh. The intermediate layer (24) contains at least Pt and a NOx storage material. The lower layer (22) has a lower layer front portion (22a) containing Pd and a lower layer rear portion (22b) containing Pd, the Pd content (C F ) in the lower layer front portion (22a) being greater than the Pd content (C R ) in the lower layer rear portion (22b). F R
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a catalyst for purifying waste gas. Background Technology

[0002] The exhaust gases emitted from internal combustion engines such as automobile engines contain hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides (NOx). x Harmful components such as HC and CO have been removed from exhaust gas. To remove these harmful components, exhaust gas purification catalysts, comprising a substrate and a catalyst layer containing a catalyst metal, are used. Exhaust gas supplied to the catalyst comes into contact with the catalyst layer, and the harmful components are purified. For example, HC and CO in the exhaust gas are oxidized and converted (purified) into water (H2O) and carbon dioxide (CO2), and NOx in the exhaust gas is reduced and converted (purified) into nitrogen (N2).

[0003] However, when an internal combustion engine starts, the catalyst used for exhaust gas purification is not yet fully warmed up, and the activity of the catalyst metal is low. Therefore, before the catalyst metal reaches the specified activation temperature, exhaust gases may be emitted with residual harmful components. To address this, sometimes the air-fuel ratio (A / F) of the supplied air-fuel mixture is made lean during engine startup, controlling the engine in a lean-burn (oxygen-excess) state—the so-called lean-burn start control—to reduce CO and HC. However, in a lean-burn atmosphere, it is difficult to extract oxygen from NOx, resulting in the inability to purify NOx.

[0004] Therefore, in order to suppress NOx emissions during the heat engine process under lean-burn start-up control, NOx storage-reduction (NSR) catalysts containing NOx storage materials are widely used (see Patent Documents 1 and 2). For example, Patent Document 1 discloses an NSR catalyst with a three-layer structure: the lower layer contains Pt and / or Pd, the middle layer contains Pt and / or Pd and NOx storage materials, and the upper layer contains Rh.

[0005] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2018-143935 Patent Document 2: Japanese Patent Application Publication No. 2016-93760 Summary of the Invention

[0006] In the catalyst layer containing NOx-absorbing materials disclosed in Patent Documents 1 and 2, a NOx absorption and storage reaction occurs under a lean-burn atmosphere. That is, NO constitutes the majority of the NOx in the exhaust gas; therefore, NO is typically oxidized first by a catalyst metal such as Pt to generate NO2. The generated NO2 reacts with the NOx-absorbing material (e.g., an alkaline earth metal) to form nitrates, which are temporarily absorbed by the NOx-absorbing material. This suppresses NOx emissions. When the atmosphere is switched to a stoichiometric ratio (scientific air-fuel ratio) to a fuel-rich (excess fuel) atmosphere, the NO2 absorbed by the NOx-absorbing material is released from the catalyst layer and reduced on the catalyst metal using reducing gases such as HC or CO as reducing agents. Thus, the NOx component in the exhaust gas is converted (purified) into nitrogen (N2).

[0007] In recent years, emissions regulations have tended to be further strengthened. Furthermore, in environmentally friendly vehicles equipped with energy-saving mechanisms, the internal combustion engine sometimes frequently stops and starts during operation. Therefore, catalysts for exhaust gas purification with NOx absorption and storage materials require further improvements in NOx absorption and storage performance under lean-burn atmospheres, i.e., further reductions in NOx emissions.

[0008] The inventors of this invention have considered using a different approach than existing technologies to improve NOx absorption and storage performance under lean-burn atmospheres. More specifically, the inventors of this invention have considered improving NOx absorption and storage performance under lean-burn atmospheres by causing the NOx absorption and storage reaction, particularly the oxidation reaction of NO, to occur as early as possible.

[0009] That is, for the aforementioned NOx uptake and storage reaction to occur, NO needs to be oxidized to NO2. However, according to the inventors' research, if CO and NO coexist, the oxidation of CO occurs preferentially, thereby hindering the oxidation of NO. The new finding is that NO2 is difficult to form, and the NOx uptake and storage reaction is delayed.

[0010] CO is primarily purified by Pd. However, in catalyst layers such as those disclosed in Patent Document 1, where the NOx adsorption material is contained in the middle layer and Pd is contained in the lower layer, CO tends to remain in the middle layer, hindering the oxidation of NO. Therefore, the inventors of this invention believe that in catalyst layers composed of a middle layer containing NOx adsorption material and a lower layer containing Pd, it is crucial to purify CO as early as possible during the heat engine process to improve NO oxidation and thus facilitate the early occurrence of the NOx adsorption reaction, in order to improve NOx adsorption performance under lean-burn atmospheres. This invention is based on this insight.

[0011] The exhaust gas purification catalyst [1] disclosed herein is an exhaust gas purification catalyst disposed in the exhaust path of an internal combustion engine for purifying exhaust gas discharged from the internal combustion engine, comprising a substrate and a catalyst layer formed on the substrate. The catalyst layer comprises a lower layer on the substrate side, an upper layer on the surface side, and a middle layer between the lower layer and the upper layer. The upper layer contains Rh. The middle layer contains at least Pt and NOx adsorption material. The lower layer has a lower layer front portion located upstream in the exhaust gas flow direction when disposed in the exhaust path, and a lower layer rear portion located downstream in the exhaust gas flow direction, the lower layer front portion and the lower layer rear portion respectively containing Pd. The content of Pd in ​​the lower layer front portion (C F The content of Pd in ​​the lower rear layer is greater than that in the aforementioned layer (C). R ).

[0012] In the catalyst for exhaust gas purification [1], the lower layer containing Pd has an upstream lower layer front and a downstream lower layer rear, and the Pd content in the lower layer front (C F The content of Pd in ​​the lower rear layer is greater than that in the lower layer (C). R That is, satisfying C. F >C R Typically, during internal combustion engine startup, the catalyst layer is heated primarily by exhaust gases, starting from the lower front portion. Therefore, by increasing the Pd content in this easily heated lower front portion (in other words, shifting the Pd concentration upstream), the CO purification reaction can occur more actively. This allows for earlier CO purification, making the NO oxidation reaction less likely to be hindered. Consequently, the NO oxidation reaction proceeds smoothly, and the NOx absorption and storage reaction occurs earlier.

[0013] Furthermore, the heat of reaction (heat capacity) during this CO purification reaction is transferred downstream along with the flow of exhaust gas, thereby improving the overall warm-up performance of the catalyst bed. As a result, the catalyst metal can be heated to the activation temperature (e.g., 200–250 °C) as early as possible. Therefore, according to the catalyst for exhaust gas purification [1], especially during the start-up of internal combustion engines, the NOx absorption and storage performance under lean-burn atmosphere can be improved.

[0014] Regarding the catalyst for exhaust gas purification disclosed herein [2], in the aforementioned catalyst for exhaust gas purification [1], the aforementioned C F Compared to the above C R The ratio (C) F / C R The following equation holds: 1.5 ≤ (C) F / C R ≤3.0. Therefore, it can also improve the NOx purification performance under stoichiometric and fuel-rich atmospheres, and reduce NOx emissions in a wide range of atmospheres from lean to fuel-rich.

[0015] Regarding the exhaust gas purification catalyst [3] disclosed herein, in the aforementioned exhaust gas purification catalyst [1] or [2], the total amount of Pd contained in each 1L of substrate in the lower layer is 3.0 g / L-cat or less. In this case, the technology disclosed herein is very effective.

[0016] Regarding the exhaust gas purification catalyst [4] disclosed herein, in any one of the aforementioned exhaust gas purification catalysts [1] to [3], the lower front layer and the lower rear layer respectively include an OSC material with oxygen absorption and storage capacity and a non-OSC material without oxygen absorption and storage capacity. The content of the non-OSC material in the lower front layer is greater than the content of the non-OSC material in the lower rear layer, and the content of the OSC material in the lower front layer is less than the content of the OSC material in the lower rear layer. Therefore, excellent exhaust gas purification performance can be maintained for a long period.

[0017] Regarding the exhaust gas purification catalyst [5] disclosed herein, in any of the aforementioned exhaust gas purification catalysts [1] to [4], the coating length in the exhaust gas flow direction of the lower front layer is shorter than the coating length in the exhaust gas flow direction of the lower rear layer. Therefore, the effects of the technology disclosed herein can be achieved at a high level, and the NOx absorption and storage performance under lean-burn atmosphere can be better improved.

[0018] Regarding the exhaust gas purification catalyst [6] disclosed herein, in any one of the exhaust gas purification catalysts [1] to [5], the coating length in the exhaust gas flow direction of the lower front layer is 30% to 60% of the total length of the substrate, and the coating length in the exhaust gas flow direction of the lower rear layer is 60% to 90% of the total length of the substrate. Therefore, it is possible to stably and effectively balance the improvement of NOx absorption and storage performance under lean atmosphere and the improvement of NOx purification performance under stoichiometric to rich atmosphere. Attached Figure Description

[0019] Figure 1 This is a schematic perspective view of a catalyst for purifying exhaust gas according to one embodiment.

[0020] Figure 2 It is Figure 1 A cross-sectional view of the catalyst used for exhaust gas purification cut off along the cylinder axis.

[0021] Figure 3 It is a schematic cross-sectional view representing the lower layer structure in Experiment I.

[0022] Figure 4 This indicates the Pd content ratio (C) F / C RA graph showing the relationship between CO and 50% purification time.

[0023] Figure 5 This indicates the Pd content ratio (C) F / C R A graph showing the relationship between NOx uptake and storage start time.

[0024] Figure 6 This is a graph showing the relationship between the 50% CO purification time and the start time of NOx absorption and storage.

[0025] Figure 7 This is a graph showing the relationship between the total amount of Pd in ​​the lower layer and the CO 50% purification time.

[0026] Figure 8 It is a graph showing the relationship between the total amount of Pd in ​​the lower layer and the start time of NOx uptake. Detailed Implementation

[0027] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. Furthermore, in this specification, matters necessary for carrying out the present invention (e.g., methods for manufacturing general catalysts for waste gas purification, etc.), except for those specifically mentioned, can be understood as design matters for those skilled in the art based on existing technology. The present invention can be implemented based on the content disclosed in this specification and common technical knowledge in the field. Additionally, in the following drawings, the same reference numerals are used to denote components and parts with the same function, and repeated descriptions are sometimes omitted or simplified. The dimensional relationships (length, width, thickness, etc.) in the drawings may not reflect actual dimensional relationships. Furthermore, in this specification, the expression "A~B" (A and B are arbitrary values) indicating a range includes both "above A and below B" and "greater than A" and "less than B".

[0028] Figure 1 This is a schematic diagram of a catalyst 100 for exhaust gas purification. The catalyst 100 is disposed within the exhaust path of an internal combustion engine to purify the exhaust gas emitted from the engine. The catalyst 100 includes a substrate 10 and a catalyst layer 20 formed on the substrate 10 (see reference). Figure 2 ). Among them, in Figure 1 In the diagram, arrow F indicates the direction of exhaust gas flow when the material is positioned within the exhaust path. Arrow X indicates the direction of the cylindrical axis of the substrate 10. X1 indicates the upstream side (front side) of the exhaust gas flow direction F, and X2 indicates the downstream side (rear side) of the exhaust gas flow direction F.

[0029] The exhaust gas purification catalyst 100 can be appropriately selected, for example, in terms of the type and shape of the substrate 10 and the design of the catalyst layer 20, and can be disposed in the exhaust system (exhaust pipe) of various internal combustion engines, especially automobile engines. Hereinafter, the exhaust gas purification catalyst 100 will be described under the premise that the internal combustion engine is a gasoline engine of an automobile, but it does not mean that the exhaust gas purification catalyst 100 is limited to this application.

[0030] <Substrate 10> The substrate 10 forms the framework of the catalyst 100 for exhaust gas purification. Various raw materials and forms of materials already used for this purpose in the prior art can be used as the substrate 10. For example, ceramics such as cordierite, aluminum titanate, and silicon carbide are preferred as raw materials due to their high heat resistance. Alternatively, a substrate made of alloy (such as stainless steel) can also be used.

[0031] Regarding the morphology, the substrate 10 here has a honeycomb structure, which has a plurality of chambers 12 regularly arranged along the cylindrical axis X (the direction of exhaust gas flow) and ribs 14 dividing the plurality of chambers 12. The chambers 12 are through holes that function as exhaust gas passages. The ribs 14 are partition walls that separate the chambers 12. The cross-sectional shape of the chambers 12 here is quadrilateral. However, the cross-sectional shape of the chambers 12 can also be other shapes (e.g., circular, triangular, hexagonal, etc.).

[0032] The substrate 10 is cylindrical in shape. However, the substrate 10 can also be other shapes (e.g., elliptical cylinder, polygonal cylinder, etc.). Furthermore, the substrate 10 is honeycomb in shape. However, the substrate 10 can also be foam, granular, etc. The volume of the substrate 10 is typically approximately 0.1 to 10 L, for example, 0.5 to 5 L. Furthermore, the total length L of the substrate 10 along the cylindrical axis X (refer to...) Figure 2 Typically, it is approximately 10 to 500 mm, for example, 50 to 300 mm. In this specification, the volume of the substrate 10 refers to the volume (apparent volume) including the volume of the internal voids such as the chamber 12, in addition to the net volume of the substrate 10.

[0033] Figure 1 The substrate 10 shown is a so-called straight-through substrate in which the inlet and outlet openings of the chamber 12 are not blocked. However, the substrate 10 can also be a so-called wall-flow (also known as wall-through) substrate in which the inlet and outlet openings of multiple chambers 12 are alternately blocked, and the exhaust gas flows from one chamber (inlet chamber) through the rib wall 14 to the adjacent chamber (outlet chamber).

[0034] <Catalyst Layer 20> Figure 2 This is a cross-sectional view of the catalyst 100 used for waste gas purification, cut along the cylinder axis X. For example... Figure 2As shown, the catalyst layer 20 is formed on the substrate 10 (specifically, the rib wall 14). However, a portion of the catalyst layer 20 can also penetrate into the interior of the rib wall 14. The catalyst layer 20 serves as the site for purifying waste gas and constitutes the main body of the waste gas purification catalyst 100. As the waste gas supplied to the waste gas purification catalyst 100 flows (passes through) within the flow path (chamber 12) of the substrate 10, it comes into contact with the catalyst layer 20. Harmful components in the waste gas are purified through contact with the catalyst layer 20.

[0035] like Figure 2 As shown, the catalyst layer 20 has a multilayer structure, specifically a three-layer structure. The catalyst layer 20 includes, in the thickness direction, a lower layer 22 located on the substrate 10 side, an upper layer 26 located on the surface portion side of the catalyst layer 20, and a middle layer 24 located between the lower layer 22 and the upper layer 26. However, the catalyst layer 20 may also include layers other than the lower layer 22, middle layer 24, and upper layer 26, to a extent that does not significantly hinder the effect of the present invention. That is, the catalyst layer 20 may also be a stacked structure with four or more layers. In this case, the lower layer 22 and the middle layer 24 are preferably connected in the thickness direction. Furthermore, the middle layer 24 and the upper layer 26 are preferably connected in the thickness direction.

[0036] The overall coating amount of catalyst layer 20 can be appropriately determined according to the type of substrate 10, and is not particularly limited. Relative to the volume of 1L substrate 10, it is, for example, 150–450 g / L-cat, preferably 200–400 g / L-cat, and more preferably 250–350 g / L-cat. In this specification, the unit [g / L-cat] represents the content contained per unit volume of one substrate.

[0037] The coating length of the multilayer structure (especially the 3-layer structure) portion of the catalyst layer 20, i.e., the average coating length along the cylindrical axis X of the substrate 10, can be, for example, 60% or more of the total length L of the substrate 10 along the cylindrical axis X, or 70% or more, 80% or more, 90% or more, or 100% of the total length L. Furthermore, in Figure 2 In the diagram, the lower layer 22, the middle layer 24, and the upper layer 26 are illustrated with the same coating length. However, the lower layer 22, the middle layer 24, and the upper layer 26 can also have different coating lengths as long as they are stacked in at least a portion of the cylinder axis direction X, with 3 layers.

[0038] The coating thickness of the multilayer structure (especially the 3-layer structure) portion of the catalyst layer 20, i.e., the average thickness in the direction perpendicular to the cylinder axis X, can be, for example, 3–300 μm, 5–200 μm, or 10–100 μm. Furthermore, in… Figure 2In the illustration, the lower layer 22, middle layer 24, and upper layer 26 are shown with the same thickness, but they can also have different thicknesses. The coating thickness of the lower layer 22 is, for example, 10–30 μm, preferably 15–25 μm; the coating thickness of the middle layer 24 is, for example, 40–60 μm, preferably 45–55 μm; and the coating thickness of the upper layer 26 is, for example, 20–40 μm, preferably 25–35 μm, but there are no particular limitations. Furthermore, the coating thicknesses of the lower layer 22, middle layer 24, and upper layer 26 can be uneven. For example, the lower layer 22 may have a thicker coating at its center in the axial direction X.

[0039] The catalyst layer 20 contains at least (1) a catalyst metal and (2) a NOx adsorbent material. Preferably, the catalyst layer 20 also contains (3) an oxygen adsorbent material (OSC material) with oxygen adsorbent storage capacity and / or (4) a non-OSC material without oxygen adsorbent storage capacity. The OSC material and / or non-OSC material can be contained in the catalyst layer 20 as a support for the catalyst metal, or they can be contained in the catalyst layer 20 in a form without supporting the catalyst metal. Furthermore, the catalyst layer 20 can also be composed primarily of OSC material and / or non-OSC material (comprising more than 50% by mass of the total component).

[0040] (1) The catalyst metal must contain three noble metals (PGMs) belonging to the platinum group: rhodium (Rh), palladium (Pd), and platinum (Pt). In addition to these three, the catalyst metal may further contain various metals that function as oxidation and / or reduction catalysts in purifying harmful components of waste gas. Examples of PGMs other than those mentioned above include ruthenium (Ru), osmium (Os), iridium (Ir), or iron (Fe), cobalt (Co), nickel (Ni) belonging to the iron group, gold (Au), silver (Ag), copper (Cu), etc. The catalyst metal is typically supported on a carrier (e.g., OSC materials and / or non-OSC materials described later). Preferably, the catalyst metal is contained in each of the lower layer 22, middle layer 24, and upper layer 26. It is preferable that the types of catalyst metals that form the main body differ in each of the lower layer 22, middle layer 24, and upper layer 26. Furthermore, the correspondence between each layer and the types of catalyst metals will be explained later.

[0041] From the viewpoint of increasing the contact area with the exhaust gas, the catalyst metal is preferably a particle with a sufficiently small particle size. The average particle size of the catalyst metal is, for example, 1 to 15 nm, preferably 1 to 10 nm, and more preferably 1 to 5 nm. The average particle size of the catalyst metal can be determined by acquiring a transmission electron microscope (TEM) image of the catalyst metal and using it as the average of the particle sizes of arbitrarily selected 50 or more catalyst metal particles in the image.

[0042] The total amount of catalyst metal contained in the catalyst layer 20 can be appropriately determined based on factors such as the volume and application of waste gas and the type of catalyst metal, and is not particularly limited. Relative to the volume of the substrate 10, it is, for example, 0.5 g / L-cat or more, preferably 1.0 g / L-cat or more, and more preferably 2.0 g / L-cat or more. On the other hand, the total amount of catalyst metal contained in the catalyst layer 20 relative to the volume of the substrate 10 is, for example, 8.0 g / L-cat or less, preferably 7.0 g / L-cat or less, and more preferably 6.0 g / L-cat or less.

[0043] As the NOx storage material (2), well-known materials used for such applications in the prior art can be used. The NOx storage material typically contains at least one of an alkali metal element and an alkaline earth metal element as the NOx storage element. Examples include compounds containing the at least one NOx storage element and in the form of carbonates or oxides, or combinations thereof. Examples of alkali metal elements include Li, K, Cs, etc., with K being preferred. Examples of alkaline earth metal elements include Mg, Sr, Ba, etc., with Ba being preferred. The NOx storage material must be included in the middle layer 24.

[0044] The total amount of NOx adsorption and storage material contained in the catalyst layer 20 is not particularly limited, but is preferably 100 g / L-cat or less, for example, 10 to 50 g / L-cat, relative to the volume of the substrate 10 per 1L.

[0045] As for the OSC material (3), any known material used for such applications in the prior art can be used. Examples include cerium oxide (Ceria, CeO2) and composite oxides containing cerium oxide, such as composite oxides containing cerium oxide and zirconium oxide (cerium oxide-zirconia composite oxide, so-called CZ composite oxide (also called ZC composite oxide)). From the viewpoint of suppressing thermal degradation of cerium oxide, it is preferable that the OSC material contains CZ composite oxide, and more preferably that it is substantially composed of CZ composite oxide (accounting for more than 95% by mass of the total, the same below). From the viewpoint of preventing oxygen depletion, it is preferable that the OSC material is contained in each of the lower layer 22, the middle layer 24, and the upper layer 26.

[0046] From the perspective of improving heat resistance and oxygen absorption / desorption properties, OSC materials (such as CZ composite oxides) can be based on cerium oxide and zirconium oxide, and further contain other additives. Examples of possible additives in OSC materials include oxides containing rare earth elements, alkali metals, alkaline earth metals, transition metals, Si, Al, etc. Examples of rare earth elements include Sc, Y, La, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, etc. Preferred rare earth oxides are Pr₂O₃, Nd₂O₃, La₂O₃, and Y₂O₃. The additives can be polycrystalline or monocrystalline.

[0047] When the OSC material contains cerium oxide, from the viewpoint of fully utilizing its oxygen uptake and storage capacity, the proportion of cerium oxide in the overall OSC material is preferably 10% by mass or more, more preferably 25% by mass or more. On the other hand, from the viewpoint of moderately suppressing the alkalinity of the OSC material, the proportion of cerium oxide is preferably 90% by mass or less, more preferably 75% by mass or less.

[0048] The total amount of OSC material contained in the catalyst layer 20 is not particularly limited, but is preferably 45 to 250 g / L-cat, more preferably 80 to 200 g / L-cat, relative to the volume of the substrate 10 per 1L.

[0049] As for (4) the non-OSC material, materials known in the prior art for such applications can be used. Among these, from the viewpoint of highly dispersed support of catalyst metals, inorganic porous bodies with large specific surface areas and excellent heat resistance are preferred. Examples include alumina (Al2O3), titanium oxide (TiO2), zirconia (ZrO2), and silicon oxide (SiO2). Among these, from the viewpoint of particularly excellent heat resistance, non-OSC materials containing alumina are preferred, and those substantially composed of alumina are more preferred. From the viewpoint of improving heat resistance and durability, non-OSC materials are preferably contained in each of the lower layer 22, the middle layer 24, and the upper layer 26.

[0050] From the perspective of improving heat resistance, non-OSC materials (such as alumina) can contain additives such as oxides of rare earth elements such as Pr2O3, Nd2O3, La2O3, and Y2O3.

[0051] The total amount of non-OSC material contained in the catalyst layer 20 is not particularly limited, but is preferably 100 to 370 g / L-cat, more preferably 170 to 300 g / L-cat, relative to the volume of the substrate 10 per 1L.

[0052] In addition to the components described in (1) to (4) above, catalyst layer 20 may further contain auxiliary materials. These auxiliary materials may be used, for example, to inhibit sintering or poisoning of the catalyst metal, or to increase the oxygen uptake capacity of the OSC material. As auxiliary materials, known materials used for such applications in the prior art can be used. Examples include monomers, alloys, and compounds (e.g., oxides, sulfates, carbonates, nitrates, chlorides) of metals containing one or more of the following elements: alkali metals, alkaline earth metals, rare earth metals, and transition metals. Layers containing auxiliary materials will be described later.

[0053] The following provides a detailed description of each of the three layers included in the catalyst layer 20: the lower layer 22, the middle layer 24, and the upper layer 26.

[0054] <Lower Level 22> like Figure 2 As shown, the lower layer 22 is formed directly on the surface of the substrate 10. In this embodiment, the lower layer 22 has a lower layer front portion 22a located on the upstream side X1 of the exhaust gas flow direction F, and a lower layer rear portion 22b located on the downstream side X2 of the exhaust gas flow direction F, which is closer to the lower layer front portion 22a than the lower layer front portion 22a. The lower layer front portion 22a is provided along the cylindrical axis direction X from the end of the upstream side X1 of the substrate 10. The lower layer rear portion 22b is provided along the cylindrical axis direction X from the end of the downstream side X2 of the substrate 10. The lower layer 22, especially the lower layer front portion 22a, functions as a CO purification layer, for example, in a lean-burn atmosphere during lean-burn start-up control.

[0055] The lower front layer 22a and lower rear layer 22b each contain Pd as a catalyst metal. Pd exhibits particularly high oxidation activity among catalyst metals, resulting in excellent CO purification performance. By placing Pd in ​​the lower layer 22, which is easily heated during startup, the CO purification reaction can proceed well under lean-burn start-up control. Furthermore, oxidation catalysts such as Pd are susceptible to the effects of poisoning substances (e.g., sulfur) contained in the exhaust gas. Therefore, by placing Pd in ​​the lower layer 22, which is far from the upper layer 26 where poisoning substances easily adhere, contact between Pd and poisoning substances can be suppressed.

[0056] The total amount of Pd contained in the lower layer 22 is not particularly limited, but relative to the volume of the substrate 10, it is, for example, 0.1 g / L-cat or more, 0.5 g / L-cat or more, preferably 1.0 g / L-cat or more, and more preferably 2.0 g / L-cat or more. This allows the CO purification reaction to occur more actively during lean-burn start-up control, enabling the technical effects disclosed herein to be achieved at a high level. On the other hand, relative to the volume of the substrate 10, the total amount of Pd contained in the lower layer 22 is, for example, 5.0 g / L-cat or less, preferably 4.0 g / L-cat or less, more preferably 3.0 g / L-cat or less, and may also be 2.9 g / L-cat or less, or 2.5 g / L-cat or less. In this case, the CO purification reaction during lean-burn start-up control becomes slow, and the oxidation reaction of NO is particularly easily hindered. Therefore, the technology disclosed herein is particularly effective.

[0057] In this embodiment, the Pd content (C) in the lower front part 22a is... F The content of Pd in ​​the lower rear 22b is greater than that in C. R That is, satisfying C. F >C R In other words, the Pd content (C) in the lower front layer 22a F The Pd content relative to the lower rear 22b (C) R The ratio of (C) F / C R ) satisfies the following formula: 1 < (C F / C R By increasing the Pd content in the lower front layer 22a, which is easily heated during startup, the CO purification reaction can occur more actively. This allows for earlier CO purification and facilitates the smooth initiation of the NO oxidation reaction. Furthermore, the heat of reaction (heat capacity) during the CO purification reaction is transferred downstream along with the exhaust gas flow, thereby improving the overall warm-up performance of the catalyst bed. As a result, the catalyst metal can be heated to its activation temperature earlier. Therefore, especially during internal combustion engine startup, NOx can be prevented from passing through the exhaust gas purification catalyst 100 and being emitted as emissions.

[0058] In this specification, "content" refers to the content (g / L) of a specific substance relative to the volume of substrate per unit volume in the portion coated with the catalyst layer. Hereinafter, the Pd content (C) of the front portion 22a of the following layer... FTaking the example of a sample, the measurement procedure is explained. In this measurement, firstly, scanning electron microscopy (SEM) is used to determine the lower front layer 22a, and its total length (coating length) La is calculated. Next, only the lower front layer 22a is cut out to a specified length L1 and pulverized into powder. Inductively coupled plasma (ICP) analysis is performed on the powder to determine the Pd weight w1 (g) relative to the specified length L1. Then, the total Pd weight W (g) of the lower front layer 22a is calculated according to the following formula: W = (w1 × La) / L1. Next, the substrate volume Va (L) of the portion coated with the lower front layer 22a is determined. The substrate volume Va of the portion coated with the lower front layer 22a is the substrate volume V (L) multiplied by the ratio of the coating length La of the lower front layer 22a to the substrate length L (i.e., substrate volume V × coating length La / substrate length L). Therefore, the Pd content (C) of the lower front layer 22a is determined. F The Pd content (in g / L) is calculated by dividing the total Pd weight W (g) of the lower front layer 22a by the volume Va (L) of the lower front layer 22a. The substrate volume V is calculated by multiplying the substrate length by the substrate cross-sectional area, and the substrate cross-sectional area is calculated by multiplying pi by the square of the substrate radius. Furthermore, in the following description, when referred to simply as "content," it refers to a value measured using the same procedure as described above for "Pd content of the lower front layer 22a." That is, in this specification, the unit [g / L] represents the amount of substrate per unit volume in the portion coated with the catalyst layer.

[0059] From the perspective of maximizing the technical effects disclosed herein, the above-mentioned ratio (C) F / C R The ratio (C) is preferably 1.2 or higher, more preferably 1.5 or higher. On the other hand, the above ratio (C) F / C R There is no specific upper limit to the ratio (C), but when the above ratio reaches a certain level, the technical effect disclosed herein tends to saturate. Therefore, the above ratio (C) F / C R The value is generally below 10, below 5.0, preferably below 4.0, more preferably below 3.5, and can also be below 3.0.

[0060] Among them, the above ratio (C) F / C R The following formula is preferred: 1.2 ≤ (C) F / C R )≤3.5, more preferably satisfying the following formula: 1.5≤(C F / C R )≤3.0, with particular preference given to satisfying the following formula: 1.5≤(C F / C RThe NOx emission level is ≤2.0. Therefore, it can improve NOx purification performance under stoichiometric and fuel-rich atmospheres. Consequently, it can reduce NOx emissions in a wide range of atmospheres, from lean to fuel-rich.

[0061] Pd content (C) in the lower front layer 22a F The concentration of Pd in ​​the lower front layer 22a is not particularly limited, but is generally 0.1 g / L or more, 0.5 g / L or more, preferably 1.0 g / L or more, more preferably 2.0 g / L or more, and particularly preferably 2.5 g / L or more. This improves NOx absorption and storage performance under a lean atmosphere, enabling the technical effects disclosed herein to be achieved at a high level. Regarding the Pd content (C...) in the lower front layer 22a... F When the content of catalyst metal is too high, the technical effect disclosed herein tends to saturate, or the catalyst metal is prone to particle growth, since it can be 6.0 g / L or less, preferably 5.0 g / L or less, more preferably 4.0 g / L or less, or 3.5 g / L or less.

[0062] Pd content (C) in the lower rear part 22b R There are no particular limitations, but the concentration is generally above 0.1 g / L, above 0.5 g / L, and preferably above 1.0 g / L. This improves NOx purification performance under stoichiometric conditions and a fuel-rich atmosphere. Regarding the Pd content (C) in the lower rear section 22b... R When the content of catalyst metal is too high, it is disadvantageous in terms of cost, so it can be 4.0 g / L or less, preferably 3.0 g / L or less, more preferably 2.0 g / L or less, and for example 1.5 g / L or less.

[0063] The lower front layer 22a and / or the lower rear layer 22b may also contain catalyst metals other than Pd. For example, noble metals (PGMs) belonging to the platinum group, as described above, can be listed. Among these, Pt, which has high oxidation activity, is preferred. In the lower front layer 22a and the lower rear layer 22b, the proportion of Pd in ​​the total catalyst metal is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably the catalyst metal is substantially composed of Pd.

[0064] The lower front layer 22a and the lower rear layer 22b preferably each contain non-OSC materials. The non-OSC materials can be supports for catalyst metals such as Pd, or they can be in a form without supporting catalyst metals such as Pd. The non-OSC materials can be the first component (the component with the highest proportion by mass) of the lower front layer 22a and the lower rear layer 22b. Preferably, the content of non-OSC materials in the lower front layer 22a is greater than the content of non-OSC materials in the lower rear layer 22b. This improves the heat resistance and durability of the lower front layer 22a.

[0065] The content of non-OSC material in the lower front portion 22a is not particularly limited, but is preferably 40-110 g / L, more preferably 50-100 g / L, and for example 60-90 g / L. The content of non-OSC material in the lower front portion 22a is preferably 10 g / L or more, and further 20 g / L or more, greater than the content of non-OSC material in the lower rear portion 22b. The content of non-OSC material in the lower rear portion 22b is not particularly limited, but is preferably 20-90 g / L, more preferably 30-80 g / L, and for example 40-70 g / L.

[0066] Preferably, the lower front layer 22a and the lower rear layer 22b each contain OSC material. The OSC material can be a support for catalyst metals such as Pd, or it can be in a form without supporting catalyst metals such as Pd. Conversely, unlike non-OSC materials, the OSC material content in the lower front layer 22a is preferably lower than the OSC material content in the lower rear layer 22b. This improves the exhaust gas purification performance under stoichiometric and fuel-rich atmosphere conditions. The OSC material content in each layer can be determined using the same procedure as described above for the Pd content in the lower front layer 22a.

[0067] The content of OSC material in the lower front layer 22a is not particularly limited, but is preferably 1 to 60 g / L, more preferably 5 to 50 g / L, and for example 10 to 40 g / L. Preferably, the content of OSC material in the lower front layer 22a is at least 10 g / L less, at least 20 g / L less, and further at least 30 g / L less than the content of OSC material in the lower rear layer 22b. The content of OSC material in the lower rear layer 22b is not particularly limited, but is preferably 20 to 90 g / L, more preferably 30 to 80 g / L, and for example 40 to 70 g / L.

[0068] The lower front layer 22a and / or the lower rear layer 22b may also contain auxiliary materials or NOx absorption materials as described above. For example, by containing alkaline earth elements (such as Ba), poisoning of catalyst metals, especially oxidation catalysts such as Pd, can be suppressed. Furthermore, the improved dispersibility of the catalyst metal can suppress catalyst metal sintering. In addition, for example, by containing alkaline earth elements together with the OSC material, the oxygen absorption capacity of the OSC material can be increased under a lean-burn atmosphere. Moreover, by containing NOx absorption materials, the NOx absorption capacity can be increased under a lean-burn atmosphere.

[0069] In the lower front layer 22a and / or the lower rear layer 22b, the content of auxiliary materials and / or NOx adsorption materials is not particularly limited, but is preferably 30 g / L or less, more preferably 20 g / L or less, and for example, 10 g / L or less. In the lower front layer 22a and the lower rear layer 22b, the content of auxiliary materials and / or NOx adsorption materials can be substantially the same (approximately within ±10%, for example, within ±5%). The content of auxiliary materials and / or NOx adsorption materials in each layer can be determined using the same procedure as described above for the "Pd content in the lower front layer 22a".

[0070] The amount of coating applied to the front portion 22a and the rear portion 22b of the lower layer is not particularly limited, but is preferably, for example, 50 to 250 g / L, more preferably 70 to 200 g / L, and even more preferably 80 to 150 g / L.

[0071] The coating length La of the lower front portion 22a in the exhaust gas flow direction (cylinder axis direction X) is typically shorter than the total length L of the substrate 10 in the extension direction (cylinder axis direction X). The coating length La of the lower front portion 22a is not particularly limited, but is preferably 20-70% of the total length L of the substrate 10, more preferably 30-60%, and even more preferably 40-50%, for example, less than 50%. The coating length Lb of the lower rear portion 22b in the exhaust gas flow direction (cylinder axis direction X) is typically shorter than the total length L of the substrate 10 in the extension direction (cylinder axis direction X). The coating length Lb of the lower rear portion 22b is preferably 50% or more of the total length L of the substrate 10, more preferably 60-90%, and even more preferably 70-80%. Therefore, it is possible to achieve both improved NOx absorption and storage performance under lean-burn atmospheres and improved NOx purification performance under stoichiometric to rich-burn atmospheres at a high level.

[0072] The coating length La of the lower front layer 22a is preferably shorter than the coating length Lb of the lower rear layer 22b. That is, La < Lb is preferred. This allows for a significant difference in Pd concentration between the upstream and downstream sides, causing Pd to be biased towards the upstream side, thus better achieving the aforementioned effects.

[0073] Among them, Figure 2 In the arrangement shown, La + Lb ≈ L, and the lower front portion 22a and the lower rear portion 22b are connected in the cylindrical axis direction X. However, the lower front portion 22a and the lower rear portion 22b can also be separated in the cylindrical axis direction X. Furthermore, the sum of the coating length La of the lower front portion 22a and the coating length Lb of the lower rear portion 22b (La + Lb) is preferably L ≤ (La + Lb), for example, L ≤ (La + Lb) ≤ 1.5L. That is, for example, due to reasons such as the preparation method of the slurry, the lower front portion 22a and the lower rear portion 22b may partially overlap at their central portions in the cylindrical axis direction X. In this case, it is preferable to position the lower rear portion 22b on the substrate 10 side.

[0074] <Middle Layer 24> The middle layer 24 contains Pt as a catalyst metal and the NOx adsorbent material as described above, functioning as a NOx adsorbent layer, for example, in a lean-burn atmosphere such as during lean-burn start-up control. For example, in stoichiometric to fuel-rich atmospheres, the middle layer 24 can also function as a three-way catalyst layer. Since the middle layer 24 is sandwiched between the lower layer 22 and the upper layer 26, waste gas flowing in from the upper layer 26 side, or harmful components contained in the waste gas, are easily retained. Therefore, by containing the NOx adsorbent material in the middle layer 24, NO2 is easily adsorbed and stored in a lean-burn atmosphere. Furthermore, in stoichiometric to fuel-rich atmospheres, NO2 desorbed from the NOx adsorbent material easily comes into contact with reducing gases such as HC or CO. Therefore, NOx emissions can be reduced in a wide range of atmospheres from lean to fuel-rich.

[0075] Pt exhibits particularly high oxidation performance among catalyst metals, especially excellent NO oxidation performance. Therefore, by containing Pt in the middle layer 24, NO can be oxidized to NO2 near the NOx absorption material under a lean-burn atmosphere. Furthermore, Pt is highly reactive with alkane-based HC. Therefore, by containing Pt in the middle layer 24, HC and CO can be efficiently purified, for example, under a stoichiometric to fuel-rich atmosphere. The Pt content in the middle layer 24 is not particularly limited, but is preferably 0.1–5 g / L, more preferably 0.5–3 g / L. Thus, it is possible to achieve a high level of both improved NOx absorption performance under a lean-burn atmosphere and improved HC purification performance under a stoichiometric to fuel-rich atmosphere.

[0076] The intermediate layer 24 may further contain catalyst metals other than Pt. For example, platinum group noble metals (PGMs) as described above can be listed. Among these, Pd, which has high oxidation activity, is preferred. In the intermediate layer 24, the proportion of Pt in the total catalyst metal is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably the catalyst metal is substantially composed of Pt. In cases where the intermediate layer 24 is substantially free of Pd (the content in the entire layer is approximately 5% by mass or less, preferably 1% by mass or less, more preferably 0.1% by mass or less, the same below), or where the intermediate layer 24 contains Pd and the Pd content in the intermediate layer 24 (C... m The content of Pd in ​​the lower rear 22b is less than that in C. R In this case, CO tends to remain in the middle layer 24, and the oxidation reaction of NO is easily hindered. Therefore, the technique disclosed herein is particularly effective.

[0077] The NOx adsorbent material preferably contains an alkaline earth metal element as the NOx adsorbent element, and particularly preferably contains Ba. The NOx adsorbent material is particularly preferably a compound selected from Ba oxides and Ba carbonates. The content of the NOx adsorbent material in the middle layer 24 is not particularly limited, but is preferably 1 to 60 g / L, more preferably 10 to 50 g / L, and for example 20 to 40 g / L.

[0078] The intermediate layer 24 preferably further contains OSC material. The intermediate layer 24 preferably contains both OSC material and non-OSC material. The OSC material and / or non-OSC material can be a support for catalyst metals such as Pt, or it can be in the form of a support without catalyst metals such as Pt. The OSC material can be the first component of the intermediate layer 24. The content of OSC material in the intermediate layer 24 is not particularly limited, but is preferably 60-120 g / L, more preferably 70-110 g / L, for example 80-100 g / L. Furthermore, the content of non-OSC material in the intermediate layer 24 is not particularly limited, but is preferably 1-60 g / L, more preferably 10-50 g / L, for example 20-40 g / L.

[0079] The amount of coating on the middle layer 24 is not particularly limited, but is preferably 120-200 g / L, more preferably 130-180 g / L, and even more preferably 140-170 g / L.

[0080] <Upper Level 26> The upper layer 26 contains Rh, which acts as a catalyst metal. The upper layer 26 can function as a three-way catalyst layer. For example, in a stoichiometric, fuel-rich atmosphere, the upper layer 26 functions as a NOx reduction layer. That is, when NO2 absorbed in the middle layer 24 becomes a gas and desorbs from the NOx adsorbent material, it easily moves towards the surface. Therefore, by containing Rh in the upper layer 26, which is located closer to the surface than the middle layer 24, NO2 can be efficiently removed after desorption from the NOx adsorbent material.

[0081] Rh exhibits particularly high H2 formation energy among catalyst metals and also demonstrates high ternary performance (especially NOx purification performance). Therefore, it can efficiently purify NOx, for example, under stoichiometric conditions and a fuel-rich atmosphere. The Rh content in the upper layer 26 is not particularly limited, but is preferably 0.01–1.0 g / L, more preferably 0.05–0.5 g / L.

[0082] The upper layer 26 may further contain catalyst metals other than Rh. For example, platinum group noble metals (PGMs) as described above can be included. Among these, Pd or Pt, which have high oxidation activity, are preferred. In the upper layer 26, the proportion of Rh in the total catalyst metal content is preferably 30% by mass or more, more preferably 50% by mass or more.

[0083] The upper layer 26 preferably further contains non-OSC materials. More preferably, the upper layer 26 contains both non-OSC materials and OSC materials. The OSC materials and / or non-OSC materials can be supports for catalyst metals such as Rh, or they can be in a form without supporting catalyst metals such as Rh. The non-OSC materials can be the first component of the upper layer 26. The content of non-OSC materials in the upper layer 26 is not particularly limited, but is preferably 30–100 g / L, more preferably 40–90 g / L, for example 50–80 g / L. The content of OSC materials in the upper layer 26 is not particularly limited, but is preferably 1–50 g / L, more preferably 5–40 g / L, for example 10–30 g / L.

[0084] The upper layer 26 may further contain auxiliary materials or NOx absorption materials as described above. In a preferred embodiment, the upper layer 26 is substantially free of NOx absorption materials, auxiliary materials containing alkali metal elements, and auxiliary materials containing alkaline earth metal elements.

[0085] The amount of coating on the upper layer 26 is not particularly limited, but is preferably 50-120 g / L, more preferably 60-110 g / L, and even more preferably 70-100 g / L.

[0086] <Method for Manufacturing Catalyst 100 for Waste Gas Purification> The catalyst 100 for exhaust gas purification can be manufactured, for example, by the following method, but is not particularly limited. First, a substrate 10 and a catalyst layer forming slurry for forming the catalyst layer 20 are prepared. The catalyst layer forming slurry can be prepared, for example, by mixing a catalyst metal source (e.g., a solution containing the catalyst metal in ionic form) and other components (e.g., NOx absorbent materials, non-OSC materials, OSC materials, binders, various additives, etc.) in a dispersion medium. As a dispersion medium, for example, water, or a mixture of water and a water-soluble organic solvent can be used.

[0087] The properties of the slurry (e.g., viscosity, solid content, etc.) can be appropriately determined based on the size of the substrate 10 used, the morphology of the chamber 12 or rib 14, and the required characteristics of the catalyst layer 20. Using a thickener is advantageous when adjusting the slurry viscosity. Examples of thickeners that can be used include carboxymethyl cellulose (CMC), methyl cellulose (MC), hydroxypropyl methyl cellulose (HPMC), hydroxyethyl methyl cellulose (HEMC), hydroxyethyl cellulose (HEC), and HEC-citric acid crosslinked products obtained by crosslinking HEC with citric acid, etc.

[0088] Specifically, firstly, a slurry for forming the lower layer containing a Pd source, a slurry for forming the middle layer containing a Pt source and a NOx adsorbent material, and a slurry for forming the upper layer containing a Rh source are prepared. At this time, as the slurry for forming the lower layer, a slurry for forming the front part of the lower layer with a relatively high Pd content and a slurry for forming the rear part of the lower layer with a relatively low Pd content are prepared.

[0089] Next, using a known coating method (e.g., suction coating, air purging, dip coating, etc.), a lower layer rear forming slurry is applied from the downstream end X2 of the substrate 10 to a predetermined position according to a known method, and then dried. Next, from the upstream end X1 of the substrate 10 to a predetermined position, a lower layer front forming slurry is applied according to a known method, and then dried. Then, it is fired to form the lower layer 22. For example, in the suction coating method, while one end of the substrate is immersed in the slurry, the slurry is suctioned from the other end, thereby allowing for precise adjustment of the coating length of each layer.

[0090] Next, using a known coating method, a middle layer forming slurry is applied to the lower layer 22, dried, and then fired to form the middle layer 24. Here, the middle layer 24 is formed along the entire length of the substrate. Further, using a known coating method, an upper layer forming slurry is applied to the middle layer 24, dried, and then fired to form the upper layer 26. Here, the upper layer 26 is formed along the entire length of the substrate. The drying conditions for the slurry are typically set at a temperature of 70–150°C, for example, 90–130°C, for 1–10 hours. The firing conditions are typically set at a temperature of approximately 300–800°C, for example, 400–500°C, for approximately 1–4 hours.

[0091] Applications of Catalyst 100 for Waste Gas Purification As described above, the catalyst 100 for exhaust gas purification can, for example, improve NOx absorption and storage performance under a lean-burn atmosphere during the start-up of an internal combustion engine. Furthermore, it is preferable to achieve excellent NOx purification performance under a stoichiometric ratio to a fuel-rich atmosphere. Therefore, the catalyst 100 for exhaust gas purification can be effectively used to purify exhaust gases emitted from internal combustion engines of vehicles such as automobiles or trucks, motorcycles or motorized bicycles, marine products such as ships, tankers, jet skis, personal watercraft, and outboard motors, gardening products such as lawnmowers, chainsaws, and trimmers, recreational products such as golf carts and ATVs, power generation equipment such as cogeneration systems, and waste incinerators. It is particularly suitable for vehicles such as automobiles, especially those equipped with gasoline engines.

[0092] <Exhaust Gas Purification Systems and Control Methods> The exhaust gas purification system disclosed herein includes an exhaust path connected to an internal combustion engine, an exhaust gas purification catalyst 100 disposed in the exhaust path, an air-fuel ratio adjusting device disposed upstream of the exhaust gas flow direction relative to the exhaust gas purification catalyst 100, and a control unit. The air-fuel ratio adjusting device is, for example, a fuel injection device that injects atomized fuel (HC) into the exhaust gas. The control unit is configured to control the air-fuel ratio adjusting device when the internal combustion engine starts, initiating lean-burn start-up control by adjusting the air-fuel ratio of the exhaust gas to a lean-burn state and supplying the exhaust gas purification catalyst 100. During the heat engine process of lean-burn start-up control, NOx in the exhaust gas is absorbed by the exhaust gas purification catalyst 100 (specifically, a NOx adsorbent material).

[0093] In such an exhaust gas purification system, the control unit preferably controls the air-fuel ratio adjustment device before initiating lean-burn start-up control to prepare for supplying the exhaust gas purification catalyst 100 to a state where the air-fuel ratio of the exhaust gas is adjusted to a rich-fuel state. This allows for the reduction of the oxidation catalyst (especially Pt or Pd) as preparation for NOx absorption by the NOx adsorbent material, thereby improving the oxidation performance of the oxidation catalyst. Consequently, NOx is more easily absorbed by the NOx adsorbent material, appropriately increasing the NOx adsorption capacity.

[0094] The following describes experimental examples related to the present invention, but it is not intended to limit the present invention to the following experiments.

[0095] [Experimental Example I: Evaluation of NOx absorption and storage performance under lean combustion atmosphere] In Experiment I, the Pd content in the front and rear sections of the lower layer was varied to evaluate the NOx absorption and storage performance under a lean-burn atmosphere, specifically the time to achieve 50% CO purification and the start time of NOx absorption and storage.

[0096] <Experimental Substrate> First, prepare a cylindrical cordierite honeycomb substrate (diameter: 118.4mm, total length: 114.3mm, volume: 1.26L). Designate one end of the substrate as the upstream X1 end (i.e., the end on the exhaust gas inflow side) and the other end as the downstream X2 end (i.e., the end on the exhaust gas outflow side).

[0097] <Preparation of Catalyst for Waste Gas Purification in Example 1> As Example 1, the Pd content in the front layer of the lower part is greater than that in the rear layer of the lower part for exhaust gas purification catalyst. Specifically, firstly, a catalyst containing the components shown in Table 1 and having... Figure 3The lower layer 122 has the cross-sectional shape shown. In detail, firstly, an aqueous solution of palladium nitrate as a Pd source, CZ composite oxide powder as an OSC material, Al2O3 powder as a non-OSC material, barium sulfate as an auxiliary material, and HEC as a thickener are mixed in ion-exchanged water and then ground to make the average particle size (D50) of the powder reach 5 μm, thus preparing two slurries: a slurry for forming the front part of the lower layer and a slurry for forming the rear part of the lower layer.

[0098] Next, the lower rear layer 122b is formed by applying a slurry to a region extending 75% of the total length of the substrate from its downstream end using a suction coating method, drying at 90°C for 1 hour, and then firing at 500°C for 1 hour. Similarly, the lower front layer 122a is formed by applying a slurry to a region extending 45% of the total length of the substrate from its upstream end using a suction coating method, drying at 90°C for 1 hour, and then firing at 500°C for 1 hour. Thus, as... Figure 3 The lower layer 122 shown is formed on the surface of the substrate 110, having a lower layer front portion 122a and a lower layer rear portion 122b. The lower layer front portion 122a and the lower layer rear portion 122b are located at the center of the substrate 110 in the cylindrical axial direction. Figure 3 The OL section overlaps with the rest.

[0099] In Example 1, for example, the Pd content (C) of the lower front layer 122a F The unit (g / L) is calculated as follows. That is, firstly, a lower front layer 122a is cut from the front of the substrate with a specified length L1 (e.g., 10 mm), and then pulverized into powder. Inductively coupled plasma analysis is performed on this powder. If it is determined that 0.271 g of Pd exists in the specified length L1 of the lower front layer, then the Pd content C of the lower front layer is... F The content (g / L) is calculated as 2.46 g / L using the following formula: 0.271 g / (10 mm / substrate length 114.3 mm × substrate volume 1.26 L). The content of other materials can also be calculated using the same method.

[0100] [Table 1] Next, an intermediate layer containing the components shown in Table 2 is formed on top of the lower layer. Specifically, firstly, a platinum nitrate aqueous solution as a Pt source, CZ composite oxide powder as an OSC material, Al2O3 powder as a non-OSC material, barium carbonate as a NOx absorbent, and HEC as a thickener are mixed in ion-exchanged water and then ground to achieve an average particle size (D50) of 5 μm to prepare an intermediate layer forming slurry. Next, using an impregnation coating method, the intermediate layer forming slurry is applied to the entire length (100%) of the substrate above the lower layer formed above, dried at 90°C for 1 hour, and then fired at 500°C for 1 hour to form the intermediate layer.

[0101] [Table 2] Next, an upper layer containing the components shown in Table 3 is formed on top of the middle layer. Specifically, firstly, an aqueous solution of rhodium nitrate as the Rh source, an aqueous solution of palladium nitrate as the Pd source, CZ composite oxide powder as the OSC material, Al2O3 powder as the non-OSC material, and HEC citric acid crosslinking agent as the thickener are mixed in ion-exchanged water and then ground to achieve an average particle size (D50) of 5 μm to prepare a slurry for forming the upper layer. Next, using an impregnation coating method, the slurry for forming the upper layer is coated onto the entire length (100%) of the substrate above the middle layer formed above it. After drying at 90°C for 1 hour, it is fired at 500°C for 1 hour, thereby forming the upper layer. By operating as described above, the catalyst for exhaust gas purification of Example 1 is obtained.

[0102] [Table 3] <Preparation of catalysts for exhaust gas purification in Examples 2-5 and Comparative Example 1> In addition to changing the Pd content (C) in the front part of the lower layer as shown in Table 4, F ) and the Pd content in the lower rear layer (C R Except for Example 1, the catalysts for exhaust gas purification in each example were obtained by operating in the same manner. Table 4 also shows the Pd content (C) in the lower front layer. F ) relative to the Pd content in the lower rear layer (C R The ratio of (C) F / C R ).

[0103] [Table 4] <Evaluation of CO 50% Purification Time and NOx Absorption / Storage Start Time under Lean Combustion Atmosphere> The exhaust gas purification catalysts for each example were cooled to below 100°C and then placed inside the exhaust pipe of an engine test bench. Exhaust gas (λ = 1.08, A / F = 15.7), with its temperature adjusted to 300°C using a heat exchanger, was then fed into the exhaust gas purification catalyst. The CO concentration at the location before the catalyst flowed in and after the catalyst flowed out was measured, and the 50% CO purification time under a lean-burn atmosphere (A / F = 15.7) was calculated based on this. Furthermore, the NOx concentration at the location before and after the catalyst flowed in was measured, and the NOx absorption start time under a lean-burn atmosphere (A / F = 15.7) was calculated based on this. The results are shown in Table 4.

[0104] Figure 4 The ratio of Pd content (C) F / C R The relationship between CO 50% purification time and CO 50% purification time. Figure 5 The ratio of Pd content (C) F / C R The relationship between NOx uptake and storage start time. Figure 6 This shows the relationship between the CO 50% purification time and the NOx absorption and storage start time. (See Table 4 and...) Figure 4 , Figure 5 As shown, the ratio of Pd content (C) F / C R The larger the value, the earlier the CO 50% purification time and NOx absorption and storage start time. Additionally, if... Figure 6 As shown, a positive correlation was confirmed between the CO 50% purification time and the NOx absorption and storage start time. Based on these results, it can be concluded that under a lean-burn atmosphere, increasing the Pd content in the lower front layer promotes the CO purification reaction, resulting in easier NO oxidation. Therefore, the exhaust gas purification catalyst disclosed herein can reduce NOx emissions, particularly during internal combustion engine start-up.

[0105] [Experimental Example II: Evaluation of NOx Purification Performance under a Fuel-Rich Atmosphere] In Test Example II, the NOx purification rate of the catalysts used for exhaust gas purification in Examples 1 to 5, in Test Example I, where the NOx absorption and storage start time was less than 40s, was evaluated under a fuel-rich atmosphere (A / F = 14.45).

[0106] <Evaluation of NOx purification rate under rich combustion atmosphere> The exhaust gas purification catalysts for each example were placed inside the exhaust pipe of an engine test bench. Exhaust gas, with its temperature adjusted to 460°C using a heat exchanger, flowed into the catalyst. The A / F ratio of the incoming exhaust gas was then varied, and the NOx levels before and after catalyst flow were measured when A / F = 14.45. Based on this, the NOx purification rate (%) under a fuel-rich atmosphere (A / F = 14.45) was calculated. The results are shown in Table 5.

[0107] [Table 5] As shown in Table 5, the NOx purification rate under a fuel-rich atmosphere varies with the Pd content (C). F / C R The lowest value was 3.5. This can be attributed to the excessive Pd content in the lower front layer, which caused unreacted NOx to pass through the catalyst used for exhaust gas purification and be discharged under a fuel-rich atmosphere.

[0108] On the other hand, in the ratio of Pd content (C) F / C R When the ratio of NOx to Pd is 1.5–3, the NOx purification rate reaches over 90%. This is especially true when the ratio of Pd content to Pd is [not specified in the original text]. F / C R When the ratio of Pd content is 1.5 to 2.5, the NOx purification rate is over 92%; when the ratio of Pd content is 1.5 to 2.5, the NOx purification rate is over 92%; F / C R When the ratio of Pd to C is 1.5–2, the NOx purification rate is over 94%, showing a very high value. Based on the above results, it can be concluded that the NOx purification rate is significantly higher when the ratio of Pd content (C) is 1.5–2. F / C R Setting the NOx concentration within the above range not only improves the NOx absorption and storage performance under lean-burn atmospheres, but also enhances the NOx purification performance under rich-burn atmospheres.

[0109] [Experimental Example III: Study on Total Pd and NOx Absorption and Storage Performance] In Experimental Example III, the ratio of fixed Pd content (C) showed excellent NOx absorption and storage performance under both lean-burn atmosphere and NOx purification performance under rich-burn atmosphere. F / C R The NOx absorption and storage performance was evaluated by varying the total Pd content in the lower layer to 1.5. Specifically, except for changing the Pd content in the front and rear parts of the lower layer as shown in Table 6, the catalysts for exhaust gas purification in Examples 6-8 were prepared in the same manner as Example 1 of Experimental Example I, and the time to achieve 50% CO purification and the start time of NOx absorption and storage under a lean combustion atmosphere were evaluated. The results are shown in Table 6.

[0110] Furthermore, the total Pd content per 1L of substrate contained in the lower layer can be calculated as follows. For example, in a layer having Figure 3 In Example 1, which shows the lower layer structure, the Pd content (C) of the front portion 122a of the lower layer is... F The Pd content of the lower layer is 2.46 g / L, and the coating length of the front portion 122a is 45% of the total length of the substrate. The substrate volume is 1.26 L. Therefore, the Pd content of the front portion 122a is 2.46 [g / L] × 45 [%] × 1.26 [L] = 1.395 g. Similarly, the Pd content of the rear portion 122b is 1.64 [g / L] × 75 [%] × 1.26 [L] = 1.550 [g]. That is, the Pd content of the lower layer is 1.395 [g] + 1.550 [g] = 2.945 [g]. The total Pd content of the lower layer is calculated by dividing the Pd content of 2.945 [g] by the substrate volume of 1.26 [L], resulting in 2.34 [g / L], which represents the total Pd content of each individual substrate in the lower layer. To distinguish it from the content mentioned above, the unit is marked with "-cat" and written as 2.34 [g / L-cat].

[0111] [Table 6] Figure 7 This indicates the relationship between the total Pd content of each substrate in the lower layer and the CO 50% purification time. Figure 8 This indicates the relationship between the total Pd content of each substrate in the lower layer and the NOx uptake initiation time. See Table 6 and... Figure 7 , Figure 8 As shown, in the ratio of Pd content (C) F / C R When Pd = 1.5, the disclosed technical effect decreases and tends to saturate when the total Pd content in the lower layer exceeds approximately 3 g / L-cat, specifically around 2.9 g / L-cat. This can be attributed to the fact that the lower layer contains a sufficient amount of Pd as the amount of Pd used increases. Therefore, it can be seen that when the total Pd content in the lower layer is below 3.0 g / L-cat, and further below 2.9 g / L-cat and 2.5 g / L-cat, the disclosed technical effect can be achieved at a particularly high level.

[0112] The specific examples of the present invention have been described in detail above, but they are merely illustrative and do not limit the scope of protection claimed. The technology described in the scope of protection includes various modifications and alterations to the specific examples illustrated above.

[0113] Explanation of reference numerals in the attached figures 10, 110: Substrate 12: Room 14: Rib wall 20: Catalyst layer 22, 122: Lower level 22a, 122a: Lower front layer 22b, 122b: Lower rear section 24: Middle Management 26: Upper level 100: Catalysts for waste gas purification

Claims

1. A catalyst for purifying exhaust gas, disposed within the exhaust path of an internal combustion engine, for purifying exhaust gas discharged from the internal combustion engine, characterized in that... Includes a substrate and a catalyst layer formed on the substrate. The catalyst layer includes a lower layer located on the substrate side, an upper layer located on the surface side, and a middle layer located between the lower layer and the upper layer. The upper layer contains Rh. The middle layer contains at least Pt and NOx adsorption and storage materials. The lower layer has a lower layer front portion located upstream of the exhaust gas flow direction when disposed within the exhaust path, and a lower layer rear portion located downstream of the exhaust gas flow direction. The lower front layer and the lower rear layer each contain Pd. The content C of Pd in ​​the lower front layer F The content C of Pd in ​​the lower rear layer is greater than that in the lower rear layer. R .

2. The catalyst for waste gas purification as described in claim 1, characterized in that, The C F Relative to C R The ratio (C) F / C R The following equation holds: 1.5 ≤ (C) F / C R ≤3.

0.

3. The catalyst for waste gas purification as described in claim 1 or 2, characterized in that, The total amount of Pd in ​​each 1L of substrate contained in the lower layer is less than 3.0 g / L-cat.

4. The catalyst for waste gas purification as described in claim 1 or 2, characterized in that, The lower front layer and the lower rear layer respectively include an OSC material with oxygen uptake and storage capacity and a non-OSC material without oxygen uptake and storage capacity. The content of the non-OSC material in the front part of the lower layer is greater than the content of the non-OSC material in the rear part of the lower layer, and, The content of OSC material in the front part of the lower layer is less than the content of OSC material in the rear part of the lower layer.

5. The catalyst for waste gas purification as described in claim 1 or 2, characterized in that, The coating length in the exhaust gas flow direction of the lower front layer is shorter than the coating length in the exhaust gas flow direction of the lower rear layer.

6. The catalyst for waste gas purification as described in claim 5, characterized in that, The coating length in the direction of exhaust gas flow at the front of the lower layer is more than 30% and less than 60% of the total length of the substrate. The coating length in the exhaust gas flow direction of the lower rear layer is more than 60% and less than 90% of the total length of the substrate.

Citation Information

Patent Citations

  • Exhaust gas purification catalyst

    JP2016093760A

  • Exhaust gas purification catalyst

    JP2018143935A